2023
DOI: 10.3390/su15032770
|View full text |Cite
|
Sign up to set email alerts
|

Study on Certification Criteria of Building Energy and Environmental Performance in the Context of Achieving Climate Neutrality

Abstract: Increased greenhouse gas emissions have led to a global warming threat. As a result, countries have tended to focus their decision-making attention on energy-saving strategies. Specifically, the concept of green building has been developed for the construction sector. It aims to create energy-efficient structural activities (new constructions, repairs, or renovated constructions) that will be carried out in line with the determined criteria. With the concept of green building and the need to establish criteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…The authors emphasized that regardless of the method used, converted LEED scores showed a positive correlation with time, suggesting that the sustainability of buildings has increased from 2006 to 2017. However, the concentration of certified LEED projects tends to be highest in areas of cities with the greatest economic potential [104]. BREEAM stands out for its inclusion of social factors, promoting community engagement and occupant wellbeing alongside environmental considerations.…”
Section: Discussionmentioning
confidence: 99%
“…The authors emphasized that regardless of the method used, converted LEED scores showed a positive correlation with time, suggesting that the sustainability of buildings has increased from 2006 to 2017. However, the concentration of certified LEED projects tends to be highest in areas of cities with the greatest economic potential [104]. BREEAM stands out for its inclusion of social factors, promoting community engagement and occupant wellbeing alongside environmental considerations.…”
Section: Discussionmentioning
confidence: 99%
“…These facts prompted the development of green building guidelines and rating systems aimed at reducing the environmental impact of buildings through sustainable design [84,85]. These guidelines and rating systems serve as technical instruments for evaluating the environmental impacts of buildings and construction projects.…”
Section: Variables Of Customer Loyalty In Micro-scale Retailingmentioning
confidence: 99%
“…In energy terms, waste management and energy consumption are very prominent in the construction process [111], and they have objectives related to creating ideal IEQ conditions that can co-occur with the active participation of occupants in improving site conditions [112]. Among the evaluation alternatives, benchmarks can be used to investigate water capacity, energy capacity and even carbon intensity [2,113]. By analyzing these conditions, it becomes possible to explore the ideal design of sustainable environments [114] and better use of resources [115].…”
Section: Environmental Impact and Risk Assessment For Sustainable Bui...mentioning
confidence: 99%
“…According to Gallo and Romano [125], urban areas consume around 75% of all global energy resources, resulting in approximately 80% of polluting gas emissions, thus representing one of the main challenges facing communities. These challenges include financial constraints and citizens' expectations, as well as the need to attract investment and create job opportunities to make these locations more sustainable, attractive, efficient and livable [2]. Along the same lines, Niza et al [126] point out that the construction sector plays a significant role in emitting pollutants due to a lack of planning, excessive energy consumption for heating and waste of resources.…”
Section: Environmental Impact and Risk Assessment For Sustainable Bui...mentioning
confidence: 99%
See 1 more Smart Citation